Kekuatan Laminasi Bambu Betung Dan Kayu Akasia Sebagai Komponen Kapal Kayu - Basuki Widodo, Akhmad; Purnomo, Revanda Indra (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Wood is one type of basic material that is often used as the main material for conventional shipbuilding in Indonesia. However, the use of wood as a material for making wooden ships is more often than trees that are proven to be sturdy but are not yet at harvest age. Bamboo is a material that is quite flexible and strong as a basic material for making wooden boats in Indonesia. Bamboo laminate combined with wood material can affect the normal bending strength of wood. This research aims to determine the effect of the ratio of bamboo laminate as a stress barrier in wood on the bending strength of the combined laminate. The method used in this research is an experimental method of the number of ratios of betung bamboo laminate constituents to acacia wood using a bending machine test, from a ratio of 40% betung bamboo to 60% acacia wood, 50% betung bamboo to 50% acacia wood, and 60% betung bamboo. % with 40% acacia wood using JIS Z-2113 standards. In this research, the results obtained were that laminates with a ratio of 40% betung bamboo to 60% acacia wood had an average bending strength value of 321.04 kg/cm2 and an average elastic modulus of 22.32 kg/cm2. The bending strength of betung bamboo laminate with acacia wood increased at a ratio of 40% betung bamboo 60% wood and decreased at a ratio of 60% betung bamboo 40% wood. The highest bending strength value is in the laminate with a ratio of 40% betung bamboo 60% acacia wood.